Case Report: Hypertrophic cardiomyopathy with recurrent episodes of ventricular fibrillation and concurrent sinus arrest - Hamidi, Jassin; Winter, Joachim; Weber, Rene; Dittmann, Sven; Schulze-Bahr, Eric (Frontiers in Cardiovascular Medicine, 2023)
Background Hypertrophic cardiomyopathy (HCM) is a serious hereditary cardiomyopathy. It is characterized morphologically by an increased left ventricular wall thickness and mass and functionally by enhanced global chamber function and myocellular contractility, diastolic dysfunction, and myocardial fibrosis development. Typically, patients with HCM experience atrial fibrillation (AF), syncope, and ventricular fibrillation (VF), causing severe symptoms and cardiac arrest. In contrast, sinoatrial node (SAN) arrest in the setting of HCM is uncommon. In particular, during VF, it has not been described so far. Case summary In this study, we report an 18-year-old woman patient with sudden cardiac arrest due to VF and successful cardiopulmonary resuscitation as the first clinical manifestation of non-obstructive HCM. Subsequently, a subcutaneous implantable cardioverter-defibrillator (ICD) was implanted for secondary VF prophylaxis. However, additional episodes of VF occurred. During these, device interrogation revealed a combined occurrence of VF, bradycardia, and SAN arrest, requiring a device exchange into a dual-chamber ICD. A heterozygous, pathogenic variant of the MYH7 gene (c.2155C>T; p.Arg719Trp) was identified as causative for HCM. Discussion First published in 1994, the particular MYH7 variant (p.Arg719Trp) was described in HCM patients with a high incidence of premature cardiac death and a reduced life expectancy. Electrophysiological studies on HCM patients are mainly performed to treat AF and ventricular tachycardia. Further extraordinary arrhythmic phenotypes were reported only in a few HCM patients. Taken together, the present case with documented co-existing VF and SAN arrest is rare and also emphasizes addressing the presence of SAN arrest (in particular, during VF episodes) in HCM patients when a distinct ICD device is considered for implantation.